2011
DOI: 10.1177/1078155211402107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vancomycin pharmacokinetics in the adult acute myeloid leukemia population

Abstract: Current vancomycin dosing guidelines in our acute myeloid leukemia population too often achieve suboptimal initial drug concentrations. Our aim was to assess vancomycin pharmacokinetic parameters in acute myeloid leukemia patients and develop an improved dosing equation to attain more accurate initial therapeutic trough levels. Acute myeloid leukemia patients receiving vancomycin for a presumed or documented gram positive infection were eligible. Patients hospitalized in the intensive care unit, those with cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
17
1
1
Order By: Relevance
“…The vancomycin particle has a molecular weight of 1,450 and has structural chemical groups for essential conjugation with other compounds [ 25 ]. Some authors have reported measurable vancomycin concentrations in the bile after intravenous administration of vancomycin, which also supports the possibility of an extrarenal path for vancomycin elimination [ 26 ].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The vancomycin particle has a molecular weight of 1,450 and has structural chemical groups for essential conjugation with other compounds [ 25 ]. Some authors have reported measurable vancomycin concentrations in the bile after intravenous administration of vancomycin, which also supports the possibility of an extrarenal path for vancomycin elimination [ 26 ].…”
Section: Discussionmentioning
confidence: 75%
“…In some earlier pharmacokinetic studies, it was suggested that patients with malignancy had increased clearance of vancomycin [ 25 ]. Conversely, other authors reported that patients with acute myeloid leukemia had lower clearance of vancomycin [ 26 ]. It was also noted that body weight may affect clearance of vancomycin, as an increase in weight was related to higher values of both clearance and volume of distribution [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Determination of an optimal initial vancomycin dosing-regimen is crucial to reach recommended serum concentrations as quickly as possible because it could results in better bacterial eradication and improved outcome. [ 4 ] The observed intra and inter-patient variability in vancomycin pharmacokinetics led to the integration of vancomycin therapeutic drug monitoring and pharmacokinetic approaches into standard practice. [ 4 5 6 ] Hence, without considering vancomycin pharmacokinetic characteristics in this specific population of patients, initial empirical vancomycin treatment may not be optimal.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] The observed intra and inter-patient variability in vancomycin pharmacokinetics led to the integration of vancomycin therapeutic drug monitoring and pharmacokinetic approaches into standard practice. [ 4 5 6 ] Hence, without considering vancomycin pharmacokinetic characteristics in this specific population of patients, initial empirical vancomycin treatment may not be optimal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation